Long-term variability of water temperature and salinity at the Polish coast - Świątek, Małgorzata (Bulletin of Geography. Physical Geography Series, 2019)
The variability of surface water temperature and water salinity at the south coast of the Baltic in the years 1950–2015 was studied in the article. To that aim, monthly surface water temperature values in Świnoujście, Międzyzdroje, Kołobrzeg (from 1957), Władysławowo, Hel and Gdynia were used, as well as monthly water salinity values in Międzyzdroje, Władysławowo, Hel and Gdynia, all obtained from IMGW-PIB (Institute of Meteorology and Water Management – National Research Institute). Linear regression and Pearson’s simple correlation coefficient of individual monthly, seasonal and annual series of temperature and salinity values over time (in subsequent years) were used to analyse the temporal changes of the examined parameters. In the analysed period a rise in the annual water temperature was recorded in Międzyzdroje, Władysławowo, Hel and Gdynia, while the extent of the changes increased towards the east. There were also positive trends in temperature values in individual months. At the same time, there was a decrease in water salinity, which was also found to be most distinct in the eastern part of the coast. In Władysławowo, Hel and Gdynia, statistically significant drops occurred in nearly all months. During the months featuring statistically insignificant trends, the observed change trends were also negative. Concurrent water temperature increases and water salinity decreases consequently caused a decline in sea water surface density at the Polish Baltic coast.